2018
DOI: 10.1039/c7dt03706f
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the structural and electronic nature of chemically exfoliated molybdenum disulfide nanosheets in aqueous dispersions

Abstract: Chemical exfoliation of molybdenum disulfide (2H-MoS) for preparing high-yield single-layer sheets has attracted considerable attention in recent years. However, the stability and nature of the resulting nanosheets are poorly understood. Storing the dispersion in ambient air brings about the reoxidation of the nanosheets, releasing their residual negative charges into the environment. The reoxidation facilitates lateral fractures and destabilizes the dispersion. In-plane X-ray diffraction of the nanosheets ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Continued degradation was observed in alkaline (LiOH, pH ≈ 11.5) samples, while precipitation of MoS 2 nanosheets (Figure S1 inset) was found in neutral (Milli-Q) cases with the supernatant displaying a light-yellow color, which later on turned blue. The precipitation phenomenon was observed and studied by Nurdiwijayanto et al It is also worth pointing out that strong absorption in the UV region was detected in the blue supernatant (Figure S1). Simply by preparing the fresh sample at a more diluted concentration, the precipitation effect can be reduced.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Continued degradation was observed in alkaline (LiOH, pH ≈ 11.5) samples, while precipitation of MoS 2 nanosheets (Figure S1 inset) was found in neutral (Milli-Q) cases with the supernatant displaying a light-yellow color, which later on turned blue. The precipitation phenomenon was observed and studied by Nurdiwijayanto et al It is also worth pointing out that strong absorption in the UV region was detected in the blue supernatant (Figure S1). Simply by preparing the fresh sample at a more diluted concentration, the precipitation effect can be reduced.…”
Section: Resultsmentioning
confidence: 68%
“…In 2015, Knirsch et al reported the observation of MoO 2 and MoO 3 formed in 1T-MoS 2 dispersion over the course of one to two months, coupled with the phase restoration from 1T to 2H . More recently, Nurdiwijayanto et al reported that 1T-MoS 2 sheets aggregated and restacked in aged aqueous dispersions where they considered the effect of Li contents and gaseous environment (oxygenated vs. oxygen-free dispersion) . According to their study, the resulting aggregates remained in the 1T polymorph but aggregated because of a continuous reduction in the magnitude of the zeta potential which destabilized the dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 1T-phase MoS 2 on the restacked Ti 0.87 O 2 0.52− was confirmed by electron diffraction (ED) analysis (Figure 3c), as indicated by in-plane diffraction rings of 11 and 32 based on a plausible 2D √3 × 1 superstructure. 43,44 In contrast, high-resolution TEM only showed the lattice fringes from the restacked Ti 0.87 O 2 0.52− with an average interlayer spacing of ∼1 nm. We performed observations over 20 different locations and did not detect any restacked MoS 2 nanosheets, which should show a smaller spacing of ∼0.6 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Exfoliation was achieved by treating the lithiated product with water under ultrasonication and then centrifuging at 2000 rpm to remove the unexfoliated crystals. The successful formation of the 1T-type MoS 2 nanosheets was confirmed as reported previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation